2019
DOI: 10.1029/2019jg005137
|View full text |Cite
|
Sign up to set email alerts
|

Climate Warming Does Not Always Extend the Plant Growing Season in Inner Mongolian Grasslands: Evidence From a 30‐Year In Situ Observations at Eight Experimental Sites

Abstract: Over the past three decades, a generally increased air temperature occurred at most places in Inner Mongolia. Such a climate warming, which outpaced the global average warming rate, has been reported to significantly influence the vegetation phenology across the Inner Mongolia grasslands. However, there is less evidence from in situ observations to demonstrate the effect of climate warming on grass phenology. In this study, we analyzed the trends in both climatic and grassland phenological variations using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Based on the five methods to extract SOS data from the NDVI series in temperate semi‐dry grasslands in China, the start of the growing season did not change significantly over the 1982–2015 period for the whole study area, although there was spatial variability in the temporal trends. This result is consistent with those of previous studies based on ground‐based observations and remote sensing (Hou et al., 2014; Wang et al., 2019). We found that the date of SOS displayed an advancing trend in the northern part of the study area, where the main type of vegetation is meadow steppe.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the five methods to extract SOS data from the NDVI series in temperate semi‐dry grasslands in China, the start of the growing season did not change significantly over the 1982–2015 period for the whole study area, although there was spatial variability in the temporal trends. This result is consistent with those of previous studies based on ground‐based observations and remote sensing (Hou et al., 2014; Wang et al., 2019). We found that the date of SOS displayed an advancing trend in the northern part of the study area, where the main type of vegetation is meadow steppe.…”
Section: Discussionsupporting
confidence: 93%
“…Climate change implies not only rising temperatures but also shifting temporal and spatial patterns of precipitation. Climate warming has advanced spring flushing in cold grasslands, for example, in Tibet and in geographical locations at high latitudes (Cong et al., 2012; Zhang et al., 2013), whereas in seasonally dry grasslands, less advancement and even delays in spring flushing have been observed (Ren et al., 2017; Wang et al., 2019). This scenario is mainly because spring phenology is regulated primarily by temperature in cold grasslands but by water availability in dry grasslands (Ma et al., 2019; Vico et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric ozone (O 3 ) is generated by photochemical reactions involving nitrogen oxides (NO x ) and volatile organic compounds (VOCs) under strong solar radiation (Sillman, 1999;Atkinson, 2000;Jacob and Winner, 2009). It is one of the most important air pollutants and has been of widespread concern (Wang et al, 2017;Li et al, 2019). High O 3 concentrations at the surface can not only injure human respiratory health (Gauderman et al, 2004;Lelieveld et al, 2015) but also lead to considerable damage to plants and crops, which further changes the land carbon budget (Fuhrer et al, 1997;Yue and Unger, 2014;Lombardozzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the period MAM, four images/month were assigned to each point and plotted with a locally estimated scatterplot smoother to visualize trends in physical plant conditions during the growing season in Inner Mongolia. September images range from the 6 th to the 13 th and the 5 th to the 12 th of the month (Kawamura et al, 2005;Wang et al, 2019a;Wei et al, 2020;Zhou et al, 2017). The section covering the 45 regular points was cross validated with 127 regular points covering the entire extent of the MODIS scene over September 2000-2018.…”
Section: Methodsmentioning
confidence: 99%